Strategies In Managing Horticultural Businesses In Indonesia (Article Review) - Fikriman Fikriman; Fuji Kacaya Mita; Pitriani Pitriani (Fakultas Pertanian Universitas Muara Bungo, 2023)
Indonesia is called an agrarian country because of its fertility, beauty, and natural wealth, the agricultural sector is one of the leading sectors in the economy where agriculture is a business activity that includes the cultivation of food crops, one of which is in the field of horticulture. This study aims to determine the strategy in the management, business development of horticultural products. In this review of the journal entitled